Protein-protein nanoimprinting of silk fibroin films - Brenckle, Mark A (2013)
Control of the interface between biological tissue and high technology materials is paramount for the development of future applications in biomedicine, especially in the case of implantable integrated devices for signal transduction.([1]-[3]) Such work requires careful materials design to develop devices that can efficiently perform technological functions while retaining biocompatibility and biological integration. Silk fibroin protein from the Bombyx mori silkworm has come of considerable interest in this context, owing to its attractive mechanical,([4]-[7]) biological, ([8][9]) and optical properties.([10][11]) Recent work has shown adaptation of common micro- and nano-fabrication tools to silk films,([12]-[18]) as well as silk protein secondary structure patterning techniques,([19]) leading to biocompatible and degradable electronic and photonic devices which can simultaneously act as a carrier and stabilizer for protein pharmaceuticals and other bioactive reagents.([20]-[23]) In particular, silk based nanoscale photonic devices face the challenge of sub-wavelength resolution fabrication on a soft polymeric substrate.([15][24]) Previous work introduced the possibility of direct, rapid nanoimprinting in silk for the fabrication of photonic structures by leveraging the material properties of this protein.([25])